Memoria, olvido y represión : un punto de vista psicoanalítico (2002)
ABSTRACT: Considerations about the body and the soul continue to be essential for understanding the emergent character of Psychoanalysis, without, due to this fact, falling in a psycho-physic dualism. For Psychoanalysis, memory is correlative to the concept of the unconscious, that is, to the unawareness of the subject of him/herself with respect to a wide range of representations called no declarative or procedural, complementary of what is known in neuroscience as declarative memory. Based on the emergent paradigm, Psychoanalysis deals fundamentally with the discursive, which is, always, neurobiological and chemical. Nevertheless, not all that is physic-chemical is neurobiological, neither ail that is neurobiological is discursive; the latter has its own laws, which are not reducible to the laws of an inferior level. Repression is therefore approached from the laws of language without forgetting that its mechanisms, as well as those of verbalisation, produce electrochemical and, in general, corporal effects. Salud UIS 2002; 34:188-194.